EKSPLOITASI PEKERJA ANAK DI MASA PANDEMI COVID-19 - Nopiana Mozin; Maisara Sunge (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2022)
Exploitation is very vulnerable to children's lives. Child labor is a form of exploitation that we often encounter in many areas in Indonesia, one of which is in Gorontalo. The exploitation of child labor is carried out not only by the environment and the surrounding community but also often by the parents or close relative of the victim. In addition, wanting to make the family's economic life easy during the Covid-19 pandemic is also one of the factors driving children to become victims of exploitation. State, government and society should pay attention to and protect child labor becoming the victim of exploitation. Likewise, parents must also be responsible for maintaining and maintaining children's human rights. Therefore, intervention by social workers from community and government is needed regarding how to make those categorized as children not vulnerably and easily becoming the victims of exploitation later. The purpose of study is to find out the factors influencing the child workers to become victims of exploitation during the Covid-19 pandemic and how social workers intervene the handling of child labor. The research method used was an empirical normative approach, through studying literature study and facts in the field and then analyzing the data qualitatively and descriptively. The results of study show economic and environmental factors causing child exploitation during the Covid-19 pandemic. In addition, this study also discusses the role of social workers’ intervention in this case related to child labors who are victims of exploitation in Gorontalo, through several approaches: religious, legal, journalistic approaches and so on in order to realize the fulfillment of children's rights to be protected from any exploitation.